Numerical and experimental investigation of a droplet vitrification process: A thermofluidic analysis for cryopreservation - Silva, Alisson R.S.; Copetti, Jacqueline B.; Monteiro, André C.; Gotardo, Marcelo; de Oliveira, Jeferson D.; Macagnan, Mario H.; Cardoso, Elaine M. [UNESP]; Ogliari, Karolyn (Elsevier, 2024)
One of the biggest challenges in studying vitrification protocols for small volumes of biological materials, especially the microdroplet vitrification protocol, is measuring the solidification rate, requiring equipment with a high level of technology, making it practically impossible to measure the degree of crystallization. An alternative is using mathematical models applied in computer simulations (CFD), helping to improve and develop new vitrification protocols. This study investigates the vitrification process utilizing the microdroplet method through experimental and numerical analysis. Droplets of mineralized water are deposited onto a copper substrate, temperature data is collected, and images of the process are taken with a high-speed camera. Numerical simulations are performed using ANSYS Fluent® software to analyze temperature and solidification behavior. Droplet contact angle measurements are also conducted to determine boundary conditions for numerical simulations. Mesh refinement is conducted using the Grid Convergence Index method, ensuring accuracy in computational results. The simulations employ a solidification model, considering phase enthalpy and thermal properties of the droplet, environment, and substrate. Results show good agreement between numerical and experimental data regarding solidification dynamics and temperature profiles. Furthermore, the study examines the influence of cooling surface geometry on the vitrification process. The contact area between the droplet and the surface increases by machining a cavity on the copper substrate, leading to enhanced cooling rates and reduced stabilization time. This research provides insights into optimizing vitrification processes, contributing to advancements in cryopreservation and material science applications.
Keywords: Cooling rate; Cryopreservation; Droplet vitrification; Vitrification